Circular RNA NINL accelerates the malignant progression of cervical cancer - ChengCheng Cao; HaiFeng Zhang; Ting Zhang; CuiCui Nie (Discover Oncology)
Abstract Objective The study’s aim was to explore a novel miRNA/mRNA network mediated by circNINL in cervical cancer (CC). Methods Tumor tissue specimens and normal tissue specimens of 86 CC patients were collected. CircNINL, miR-2467-3p, and specificity protein 1 (SP1) expression levels in tissues were detected. In Hela cells, transfection was implemented to determine whether CircNINL, miR-2467-3p and SP1 regulated cellular progression. The interaction between circNINL, miR-2467-3p, and SP1 was explored. Results CircNINL and SP1 were abnormally increased whereas miR-2467-3p expression was suppressed in CC. Functionally, circNINL silencing or miR-2467-3p overexpression reduced CC cell progression, whereas circNINL overexpression did the opposite. CircNINL had a spongy effect on miR-2467-3p to regulate SP1 levels. miR-2467-3p inhibition or SP1 overexpression offset the inhibitory effect of circNINL silence on CC malignant progression. Conclusion CircNINL silencing can increase miR-2467-3p, thereby inducing the downregulation of SP1, thereby suppressing CC progression.